Radiolytic Synthesis of Colloidal Silver Nanoparticles for Antibacterial Wound Dressings - Pimpon Uttayarat; Jarurattana Eamsiri; Theeranan Tangthong; Phiriyatorn Suwanmala (Advances in Materials Science and Engineering)
Radiolytic synthesis provides a convenient and environmentally-friendly approach to prepare metallic nanoparticles in large scale with narrow size distribution. In this report, colloidal silver nanoparticles (AgNPs) were synthesized by gamma radiation using poly(vinyl alcohol) (PVA) or silk fibroin (SF) as stabilizers and were evaluated for their antibacterial properties. The conversion of metallic silver ions to silver atoms depended on irradiation dose and stabilizer concentration as determined by UV-Vis spectrophotometry and transmission electron microscopy. The uniformly dispersed AgNPs with diameter 32.3 ± 4.40 nm were evaluated as antiseptic agents in films composed of chitosan, SF, and PVA that were processed by irradiation-induced crosslinking. Using disc diffusion assay, the films containing 432 ppm AgNPs could effectively inhibit the growth of both Staphylococcus aureus and Pseudomonas aeruginosa. Therefore, we have demonstrated in our present study that gamma radiation technique can potentially be applied in the mass production of antibacterial wound dressings.